Metoda redukce odlesku v kolposkopii - Měřínský, Jaroslav (Česká gynekologie, 2012)
Saving the colposcopic images on memory media is called cervicography, colpography and vulvography. The light beams create unwanted reflections which don't allow a valid survey of examined area in the real time monitoring as well as in the archiving. The solution of the problem is based on usage of a double polarization fiuters as described below.
Keywords: Colposcopy; kolposkopie; Light; Diagnostic Techniques, Obstetrical and Gynecological; světlo; diagnostické zobrazování; Diagnostic Imaging; Colposcopes; diagnostické techniky porodnicko-gynekologické; kolposkopy